An Assessment of the Assignments and Arrangements of the Executive Agent for DoD Biometrics and Status Report on the DoD Biometrics Enterprise - Shontz, Douglas (RAND Corporation, 2012)
As the need to identify known and suspected combatants has elevated the importance of biometrics in the Department of Defense (DoD), RAND researchers assessed how current activities are supporting end users and how DoD is preparing to focus biometrics on different missions. As overseas contingency operations wind down, DoD's biometrics program must move in a new direction, and continued funding must be justified in new ways.